Urinary Malondialdehyde Is Associated with Visceral Abdominal Obesity in Middle-Aged Men - Sun Min Lee; Young Hye Cho; Sang Yeoup Lee; Dong Wook Jeong; A Ra Cho; Jeong Suk Jeon; Eun-Ju Park; Yun Jin Kim; Jeong Gyu Lee; Yu Hyeon Yi; Young Jin Tak; Hye Rim Hwang; et al. (Mediators of Inflammation)
The purpose of the present study was to investigate multiple anthropometric parameters used to evaluate obesity, particularly visceral abdominal fat area, and various metabolic parameters including malondialdehyde (MDA) as an oxidative stress marker. We evaluated various measures of obesity, including body mass index (BMI), waist circumference (WC), sagittal abdominal diameter, fat percentages using dual-energy X-ray absorptiometry, visceral fat area (VFA), subcutaneous fat area, multiple biomarkers related to metabolic disease, and urinary MDA, in 73 asymptomatic middle-aged men who were not severely obese. We examined relationships between multiple measures of obesity, metabolic markers, and urinary MDA levels and evaluated associations between VFA and urinary MDA. In the visceral obesity group, γ-glutamyl transferase (GGT), uric acid, and urinary MDA levels were significantly higher than in the nonvisceral obesity group (P = 0.008, P = 0.002, and P = 0.018). Urinary MDA (r = 0.357, P = 0.002) and uric acid (r = 0.263, P = 0.027) levels were only significantly positively correlated with VFA among measures of obesity. Urinary MDA, serum GGT, and serum CRP were significantly positively associated with VFA (P = 0.001, P = 0.046, and P = 0.023, resp.), even after adjusting for BMI and WC.